(untitled) (ARQUISUR Revista, 2015)
This article assumes that in the analysis of the urban landscape should be considered in addition to aesthetics aspects, the complex social, historical and cultural processes that have made their "construction". The Largo da Mariquita, located at Rio Vermelho neighborhood of Salvador - Bahia, had its space and urban landscape transformed: from Indian village, fishing village and summerplace - in the twentieth century; the tertiary use mainly focused on tourism and tourist place nowadays. Thus, the ancient, the modern and the contemporary dialogue and are mixed at Mariquita, showing the complex relations between heritage, uses, land use and appropriation of urban space in contemporary Salvador. The purpose of this article is therefore to present and discuss some issues and possible interpretations of the urban landscape of the Largo Mariquita, considering its landscape importance, architectural, cultural and historical for the city and especially for Salvador’s population.